Key Areas to Economic Takeoff from Demographic Dividend: A Case of Nepal - Parajuli, Kewal Ram (Journal of Research and Development, 2021)
Rapid demographic change in the context of age structure and basic demographic indicators have created opportunity to accelerate economic growth and development in Nepal. At the time of favorable demographic context, it is required to qualify and mobilize currently existing large volume of active years population to fulfill the mission of sustained economic development. For this, it is necessary to invest on health, education, infrastructure along with creating employment opportunities but such opportunity period is missing out due low attention on social, economic, political and cultural sectors, which may misfortune for Nepal. Focusing on the key areas of economic take off in the declined fertility context, this paper reviews literature related to reaping demographic dividend. Based on secondary data from journal articles, census and Nepal Demographic Health Survey (NDHS) results, descriptive and content analysis method is applied. National Census data from Central Bureau of Statistics (CBS) and Nepal Demographic Health Survey (NDHS) is taken as reference and some estimation from United Nations (UN) are also taken as requirement. To identify vital areas and situation to support economic take off and support to formulate and implement proper future population policy in Nepal are the main objectives of this article. Coping with socio-economic challenges need to focus on primary area of social development like education, productivity of labor, proper use of remittance to economic take off. Need to open gate for secondary demographic dividend with appropriate policy formulation in the recent context.